2018
DOI: 10.1080/15299716.2018.1481482
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Model of Binegativity, Drinking-to-Cope Motives, Alcohol Use, and Sexual Coercion Among Self-Identified Bisexual Women

Abstract: In the present study, we tested a sequential mediation model whereby binegativity was associated with sexual coercion through drinking to cope motives and alcohol use. Data were examined from 224 self-identified bisexual women (M age = 22.79; SD = 3.44) who took part in an online survey. Participants reported binegativity, alcohol use, drinking to cope motivations, and sexual coercion experiences for the previous 30 days. A total of 48.0% of the sample (n = 108) experienced sexual coercion in the past 30 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Drinking to cope motives was high among this sample, possibly due to recruitment criteria, suggesting there may have been a ceiling effect. This premise is further supported by a higher average (15.50) and lower standard deviation (5.27) of drinking to cope motives compared to previous studies of regular drinking bisexual women with less stringent recruitment criteria (e.g., Kelley, Ehlke, Braitman, et al, 2018; Kelley, Ehlke, Lewis, et al, 2018). Although drinking to cope is commonly conceptualized as a trait level variable (e.g., Armeli et al, 2010; Dvorak et al, 2014; Simpson et al, 2014), drinking to cope motives may be dynamic, especially for risky drinkers, and fluctuate with one’s immediate experiences.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Drinking to cope motives was high among this sample, possibly due to recruitment criteria, suggesting there may have been a ceiling effect. This premise is further supported by a higher average (15.50) and lower standard deviation (5.27) of drinking to cope motives compared to previous studies of regular drinking bisexual women with less stringent recruitment criteria (e.g., Kelley, Ehlke, Braitman, et al, 2018; Kelley, Ehlke, Lewis, et al, 2018). Although drinking to cope is commonly conceptualized as a trait level variable (e.g., Armeli et al, 2010; Dvorak et al, 2014; Simpson et al, 2014), drinking to cope motives may be dynamic, especially for risky drinkers, and fluctuate with one’s immediate experiences.…”
Section: Discussionsupporting
confidence: 58%
“…An example item for the coping scale is: “To forget about your problems.” A sum score was computed and higher scores indicated greater motivations to drink to cope with negative emotions. The DMQ has been used among sexual minority samples, including bisexual women, and has shown high reliability and construct validity (e.g., Cooper, 1994; Kelley, Ehlke, Braitman, et al, 2018; Kelley, Ehlke, Lewis, et al, 2018; Lewis et al, 2016; Merrill & Read, 2010; Talley et al, 2012). Cronbach α for the coping subscale for the present study was .89.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited from social media sites (e.g., Craigslist, Reddit, Tumblr, Facebook) and the psychology research participant pool at the participating university. Criteria for participation in the larger study were as follows: (a) female, (b) self-identified as bisexual, (c) between 18 and 30 years of age, and (d) engagement in sexual behavior (e.g., touching, kissing, sex) in the past 30 days (Kelley, Ehlke, Braitman, & Stamates, in press). Eligible participants were directed to an online survey link to complete a 30-min questionnaire that included questions about alcohol use and drinking norms.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the framework proposed by Hatzenbuehler (2009), Kelley, Ehlke, Braitman, et al (2018) found evidence for a sequential mediation model whereby bisexual women who experienced more instances of binegativity reported greater experience with sexual coercion through heightened use of drinking to cope and greater frequency of subsequent alcohol use. Further, an additional study (Schulz et al, 2020) found support for a similar model whereby the experience of binegativity and alcohol-related problems were sequentially mediated by greater drinking to cope motives and alcohol use.…”
Section: Mechanisms Explaining Alcohol and Drug Use Among Bisexual Womenmentioning
confidence: 53%
“…Specifically, bisexual persons have been perceived as promiscuous (Dodge et al, 2016; Hequembourg & Brallier, 2009), disloyal (Israel & Mohr, 2004), and nonmonogamous (Hequembourg & Brallier, 2009; Klesse, 2005) by both heterosexual and lesbian/gay persons. Such stigmatization against bisexuals is described as binegativity (Yost & Thomas, 2012) and has been associated with poor health outcomes such as alcohol and drug misuse among bisexual women (Brewster & Moradi, 2010; Kelley, Ehlke, Braitman, et al, 2018; Kelley, Ehlke, Lewis, et al, 2018). Interestingly, data from the Wave 2 NESARC study indicated that gay men and lesbian women reported higher rates of sexual orientation discrimination compared to bisexual and heterosexual men and women (Evans-Polce et al, 2020); however, it may be important to consider that bisexual persons are less likely to disclose their identity (Doan & Mize, 2020), which may in-turn protect them from sexual discrimination.…”
Section: Mechanisms Explaining Alcohol and Drug Use Among Bisexual Womenmentioning
confidence: 99%